Evaluation of Jackfruit Peel Extract as a Low-Cost Medium for Spirulina platensis Culture: Evaluation of Jackfruit Peel Extract for Spirulina Platensis Culture - Hossain, Md. Amzad; Fahmida Jahan Riya; Das, Mousumi; Fouzia Sultana Bristy; Taslima Akter; Md. Shah Alam Sarker (Journal of Tropical Life Science, 2025)
Spirulina platensis is a nutrient-rich blue-green alga, ideal for use as a human food and an animal feed supplement. The Kosaric medium (KM) provides optimal biomass production for Spirulina sp.; however, it is expensive and inaccessible. This study evaluated the potential of jackfruit peel powder extract (JPE) as a low-cost source of nutrients for S. platensis cultivation. The production performance of S. platensis was evaluated for 24 days in four concentrations of JPE medium (2.5, 5, 7.5, and 10%), each supplemented with 3.0 g/l NaHCO₃ and 1.25 g/l NaNO₃. Cultivation of S. platensis with KM served as the control. Maximum cell biomass (48.27 ± 0.36 mg/l), optical density (1.51 ± 0.02), specific growth rate (0.60 ± 0.02 μg/day), chlorophyll a (5.14 ± 0.03 μg/ml), chlorophyll b (3.95 ± 0.04 μg/ml), and β-Carotene (2.58 ± 0.05 μg/ml) of S. platensis were observed in KM (control) at the 20th days of culture. Similar results were obtained at 2.5% JPE medium (cell biomass: 47.47 ± 0.49 mg/l; optical density 1.49 ± 0.02, specific growth rate: 0.58 ± 0.02 μg/day; chlorophyll a 5.09 ± 0.04 μg/ml; chlorophyll b 3.93 ± 0.04 μg/ml, β-carotene 2.55 ± 0.05 μg/ml). All the growth parameters tend to decrease gradually with the further increase in concentration of the JPE medium. JPE medium of 2.5% supplemented with NaHCO3 and NaNO3 produced comparable growth and pigment content of S. platensis to KM, suggesting its potential as a cost-effective alternative culture medium for S. platensis.